2020
DOI: 10.1088/1742-6596/1567/4/042019
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Science Technology and Society (STS) model with the help of Facebook in science learning for junior high school students

Abstract: Research has been conducted to investigate the influence of the Science Technology Society (STS) learning model which is assisted by social media Facebook (FB) in science learning. This research was conducted in a group of junior high school students in Tondano, North Sulawesi, Indonesia. The research method is a Quasi-Experiment Posttest-Only Control Group Design. The experimental group was treated with the STS learning model assisted by FB, and the control group with lectures, discussions, question, and answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…While Putra (2021) and Widiastuti and Purnawijaya (2021) only used the SETS approach without any additional strategies, the results showed that students still value science learning more than those in the non-SETS group. According to Poluakan et al (2020), in relation to STS approach subgroup, the teaching model stimulated students' interest in science learning, particularly with regard to enhancing scientific literacy, when used in conjunction with the social media platform, Facebook. As a result of the study's findings, teachers and students will interact outside of the classroom when using social media for educational purposes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While Putra (2021) and Widiastuti and Purnawijaya (2021) only used the SETS approach without any additional strategies, the results showed that students still value science learning more than those in the non-SETS group. According to Poluakan et al (2020), in relation to STS approach subgroup, the teaching model stimulated students' interest in science learning, particularly with regard to enhancing scientific literacy, when used in conjunction with the social media platform, Facebook. As a result of the study's findings, teachers and students will interact outside of the classroom when using social media for educational purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted to identify the precise outcomes of students' scientific achievements after using the STS approach (Gallagher, 1971;Dass, 2005;Chantaranima & Yuenyong, 2013;Zoller, 2013;Kapici, Akcay & Yager, 2017;Primastuti & Atun, 2018;Poluakan, Kapubau, Suryani, Sumampouw & Rungkat, 2020;Putra, 2021). Collectively, these STS-related published reports show measurable gains in student performance in terms of understanding and application of fundamental scientific principles, mastery of scientific ideas and procedures, and the ability to apply scientific ideas and procedures in novel contexts, particularly those found in real-world settings.…”
Section: Impact Of Sts Instruction and The Need For A Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, unverified information spreads fast. Today, anyone can spread news or information, so this behavior leads to misinformation (Poluakan et al 2020). Potter (2004) says media literacy helps consumers understand media.…”
Section: Introductionmentioning
confidence: 99%